High-compaction lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
By recovering LiFePO4 intermediate and introducing Mn2+, combined with a simplified synthesis process, lithium manganese iron phosphate cathode material with high compaction density, high electronic conductivity and high voltage platforms was prepared, which solved the problem of insufficient compaction density and electrical performance of existing materials, and achieved a higher energy density and voltage platform.
Patent Information
- Application Number
- CN202510010761.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium manganese iron phosphate positive electrode materials have problems such as low compaction density, low electronic conductivity, Mn3+ dissolution at high temperatures, and processing performance deviations, which are difficult to meet the needs of high energy density and high voltage platforms.
By recovering LiFePO4 intermediates, introducing Mn2+ and supplementing the corresponding phosphorus and lithium sources, a simplified synthesis process, including mixing, grinding, spray drying and sintering, lithium manganese iron phosphate positive electrode material with high compaction density, high electronic conductivity performance and high voltage platform was prepared.
The high compaction density, electronic conductivity and voltage platform of lithium manganese iron phosphate cathode material has been improved, while reducing the technical complexity and enhancing the practical and economic value of waste lithium iron phosphate.
Smart Images

Figure CN119650692A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a high-density lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Lithium iron phosphate positive electrode and graphite negative electrode as a lithium-ion battery cell chemical material system, with its high safety, low cost, long life and other characteristics, is widely used in electric vehicles, household storage, backup power supply, energy storage power stations and other fields. With the demand for long battery life and high energy density, new requirements are put forward for the voltage platform (V), compaction (g / cc), and gram capacity (mAh / g) of positive electrode materials. Olivine-type positive electrode material LiMn x Fe 1-x PO 4 (0<x<1) has good thermal stability and cycle performance, and also has high voltage characteristics and low temperature discharge performance. Its future development trend is to gradually replace LiFePO 4 , further improving the energy density and voltage platform of the battery cell. x Fe 1-x PO 4 (0<x<1) There are low compaction density, low electronic conductivity, and Mn 3+ Problems such as dissolution and processing performance deviation.
[0004] At present, the compaction density of lithium iron phosphate used in mainstream power batteries on the market is 2.50-2.65g / cc, and the corresponding powder compaction density is in the range of 2.40-2.60g / cc. The corresponding primary particle size is 50-200nm, and the surface is carbon-coated to improve electronic conductivity, TiO 2 Doping modification improves the lattice structure, and its technology is mature and has a wide range of applications. 4 / Gr chemical material system retired batteries, the current treatment methods include the following directions: cascade reuse, resource recovery, direct scrapping, among which resource recovery is mainly for Li 2 CO 3 、LiFePO 4 , Al, Cu, Gr, etc.
[0005] In summary, it is urgent to find a better method to improve the compaction density and electrical properties of lithium manganese iron phosphate. Summary of the invention
[0006] In order to improve the compaction density and electrical properties of lithium manganese iron phosphate, the present invention provides a high-density lithium manganese iron phosphate positive electrode material and its preparation method and application. 4 The intermediate is the matrix, and Mn is introduced 2+ And supplement the corresponding phosphorus source and lithium source, simplify the synthesis process, take into account the characteristics of high compaction density, high electronic conductivity, high voltage platform, etc., and at the same time enhance the practical and economic value of waste lithium iron phosphate.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention provides a method for preparing a high-density lithium manganese iron phosphate positive electrode material, comprising:
[0009] Lithium source, recovery of LiFePO 4 The intermediate, the carbon source, the dispersant and water are mixed uniformly to obtain a mixed solution A;
[0010] adding a manganese source into the mixed solution A to obtain a mixed slurry B;
[0011] Grinding the mixed slurry B and adding a phosphorus source to obtain a mixed slurry C;
[0012] The mixed slurry C is spray-dried and sintered to obtain lithium iron manganese phosphate powder;
[0013] Wherein, the recovery of LiFePO 4 The intermediate is recovered from waste lithium iron phosphate batteries.
[0014] The present invention is based on the high compaction density characteristics of lithium iron phosphate and introduces Mn 2+ Construction of LiMn x Fe 1-x PO 4 (0<x<1) structure, which takes into account LiFePO 4 (high density, high electronic conductivity) and LiMnPO 4 (high voltage platform) characteristics, while reducing technical complexity and ensuring performance.
[0015] It should be noted that the present invention is to recover LiFePO 4 The specific recovery method of the intermediate is not particularly limited, as long as the LiFePO recovered from waste lithium iron phosphate batteries 4 Intermediates are fine, for example, LiFePO recycled from waste LFP / Gr batteries 4 Intermediate.
[0016] Preferably, the manganese source is selected from at least one of manganese oxalate, manganese acetate, manganese nitrate, basic manganese carbonate, manganese monoxide, and trimanganese tetraoxide.
[0017] Preferably, after the grinding, the D50 of the particles is 250-400 nm.
[0018] Preferably, the selected phosphorus source is at least one selected from phosphoric acid, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.
[0019] Preferably, after the spray drying, the powder particle size is 15 to 30 μm.
[0020] Preferably, the sintering is carried out at 2 The content was less than 10 ppm under inert atmosphere.
[0021] Preferably, the specific steps of sintering are: first, keep warm at 200-400°C for 2-5 hours, then keep warm at 600-900°C for 3-5 hours, and finally, keep warm at 600-800°C for 5-8 hours.
[0022] Preferably, the D50 of the lithium iron manganese phosphate powder is 0.8-1.2 μm.
[0023] The second aspect of the present invention provides a high-density lithium manganese iron phosphate positive electrode material prepared by the above method.
[0024] The third aspect of the present invention provides the use of the above-mentioned high-density lithium manganese iron phosphate positive electrode material in the preparation of electric vehicles, household storage, backup power supplies, and energy storage power stations.
[0025] Beneficial effects of the present invention
[0026] (1) The present invention obtains LiFePO by recycling waste lithium iron phosphate batteries 4 Intermediates are supplemented with corresponding lithium sources, phosphorus sources, and manganese sources, and technical features such as sand grinding and sintering processes are designed. The prepared lithium manganese iron phosphate powder has the characteristics of high compaction density, high electronic conductivity, and high voltage platform of lithium iron phosphate while taking into account economic benefits.
[0027] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0029] Figure 1 45℃1C / 1C 2.0-4.4V cycle curves for the examples and comparative examples;
[0030] Figure 2 The following are SEM images of the embodiments and comparative examples. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0033] In the following examples, LiFePO was recovered 4 The intermediate is prepared by the method described in Example 1 of patent CN114243144A, comprising:
[0034] The waste lithium iron phosphate positive electrode sheets obtained by disassembling the waste lithium iron phosphate batteries are crushed into positive electrode fragments of about 2 cm*2 cm, 150 g of lithium iron phosphate positive electrode fragments are weighed into a 500 mL beaker, 300 mL of organic solvent N-methylpyrrolidone (NMP) is added to the beaker, the beaker is placed in an ultrasonic cleaner, heated to 80° C. in a water bath, and mechanically stirred for 2 hours to completely separate the positive electrode material from the current collector and completely dissolve the binder in the solvent, then the positive electrode mixed solution in the beaker is filtered to remove the current collector, the filtrate is centrifuged, and then washed with deionized water, the washing is repeated 5 times, and vacuum dried at 40° C. to obtain a mixture of failed lithium iron phosphate positive electrode material and conductive agent, i.e., lithium iron phosphate intermediate material.
[0035] Example 1
[0036] 1. Recycle a certain amount of LiFePO 4 Intermediate, Li 2 CO 3 , glucose, PEG (polyvinyl alcohol), according to the mass ratio of 1:0.35:0.1:0.1 and a certain amount of deionized water to prepare a mixed solution A with a solid content of 38%;
[0037] 2. Take a certain amount of MnO and add it to the mixture A prepared in step 1, mix and stir to obtain a mixed slurry B, in which MnO and LiFePO in step 1 4 The mass ratio is 1:0.67;
[0038] 3. Grind the mixed slurry B and add a portion of H 3 PO 4 , and obtain mixed slurry C, D50 is 350nm, where H 3 PO 4 With LiFePO in step 1 4 The mass ratio is 1:0.93;
[0039] 4. The mixed slurry C obtained in step 3 is spray dried to obtain powder D with a D50 of 20 μm;
[0040] 5. The powder D obtained in step 4 is placed in an inert atmosphere for sintering to obtain powder E. The sintering process is as follows: the temperature of the first stage is 350°C, the insulation time is 4h, the temperature of the second stage is 780°C, the insulation time is 6h, and the temperature of the third stage is 760°C, the insulation time is 8h. The required sintering is N 2 Atmosphere(O 2 Content <10ppm);
[0041] 6. The powder E in step 5 is crushed and classified to obtain the finished product LiFe 0.4 Mn 0.6 PO 4 , D50 is 1.1μm.
[0042] Example 2
[0043] 1. Recycle a certain amount of LiFePO 4 Intermediates 、 Li 2 CO 3 , glucose, PEG, according to the mass ratio of 1:0.23:0.1:0.1, and a certain amount of deionized water were prepared into a mixed solution A with a solid content of 38%;
[0044] 2. Take a certain amount of MnO and add it to the mixture A prepared in step 1, mix and stir to obtain a mixed slurry B, in which MnO and LiFePO in step 1 4 The mass ratio is 1:0.45;
[0045] 3. Grind the mixed slurry B and add a portion of H 3 PO 4 , and obtain mixed slurry C, D50 is 300nm, where H 3 PO 4 With LiFePO in step 1 4 The mass ratio is 1:0.62;
[0046] 4. The mixed slurry C obtained in step 3 is spray dried to obtain powder D with a D50 of 15 μm;
[0047] 5. The powder D obtained in step 4 is placed in an inert atmosphere for sintering to obtain powder E. The sintering process is as follows: the first stage temperature is 350°C, the insulation time is 4h, the second stage temperature is 770°C, the insulation time is 6h, and the third stage temperature is 750°C, the insulation time is 8h. The required sintering time is N 2 Atmosphere(O 2 Content <10ppm);
[0048] 6. The powder E in step 5 is crushed and classified to obtain the finished product LiFe 0.5 Mn 0.5 PO 4 , D50 is 0.9μm.
[0049] Comparative Example 1
[0050] Manganese oxalate and ferrous oxalate were dissolved in deionized water at a molar ratio of 3:2 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (the total concentration of manganese oxalate and ferrous oxalate was 0.4 mol / L); ammonium dihydrogen phosphate was dissolved in deionized water to prepare a 0.4 mol / L phosphorus source solution B (also referred to as the second solution). Solution B and solution A were mixed evenly, stirred at a speed of 200 r / min under nitrogen protection, and heated at 60°C for 15 hours to obtain a precipitated product; wherein the molar ratio of the metal ions in the first solution to the phosphorus source in the second solution was 1:1. The precipitated product is washed, filtered and dried to obtain a first precursor; the first precursor, lithium carbonate, glucose and polyvinyl alcohol are evenly mixed and placed in a nitrogen atmosphere, wherein the heating rate is 5°C / min, and the calcination is divided into two stages, the first stage calcination temperature is 550°C, the calcination time is 5h, the second stage calcination temperature is 780°C, the calcination time is 15h, and after the calcination is completed, the lithium iron manganese phosphate positive electrode material is obtained.
[0051] Comparative Example 2
[0052] Add 85% phosphoric acid to the ferrous sulfate solution, stir continuously for 0.5h, then add hydrogen peroxide at a molar ratio of ferrous solution to hydrogen peroxide = 1:1.2, use an oxidant to completely oxidize the ferrous sulfate solution to a ferric sulfate solution as an iron source, add manganese sulfate at a molar ratio of 4:6 to the iron source and mix evenly into a uniform solution. Add ammonium carbonate to adjust the pH to 5.5, stir at room temperature for 2h, and filter. Dissolve the precursor precipitate in water, stir and wash three times, and dry at 120°C to obtain a ferromanganese phosphate precursor containing sulfur crystal water. After the material is crushed, sinter it at 500°C in an air atmosphere for 6h to obtain ferromanganese phosphate particles with uniform particle size.
[0053] The ferromanganese phosphate precursor is mixed with a lithium source, a carbon source, and a phosphorus source according to a molar ratio of Li, Mn, Fe, and P of 1:0.6:0.4:1 and sand-milled; the molar mass ratio of the lithium source to the ferromanganese phosphate precursor is 1:1.02; the amount of the carbon source added is 15% of the total weight of the ferromanganese phosphate precursor and the lithium source; the amount of the phosphorus source added is 0.5% of the weight of the ferromanganese phosphate precursor; the sand-milling rate is 1000rpm / min, and the time is 50min. The spray-dried powder is transferred to a nitrogen atmosphere protection environment for sintering; the heating rate is 5℃ / min, and the calcination is divided into two stages, the first stage calcination temperature is 450℃, the calcination time is 5h, and the second stage calcination temperature is 780℃, and the calcination time is 10h. After calcination, a carbon-coated lithium ferromanganese phosphate positive electrode material is obtained.
[0054] The lithium manganese iron phosphate positive electrode material, acetylene black and binder (PVDF) prepared in the embodiment and comparative example were mixed uniformly in a mass ratio of 8:1:1, and NMP was used as a solvent and manually ground to obtain a uniformly mixed slurry. The obtained slurry was coated on an aluminum foil sheet, dried in a vacuum oven at 120°C for 10 hours, and then formed into a disc-shaped pole piece with a diameter of 8mm. This pole piece was assembled into a CR2025 button battery. At room temperature (25°C), the constant current charge and discharge test was carried out with a limiting voltage of 2 to 4.5V, wherein the cycle test voltage range was 2.0 to 4.4V and the test temperature was 45°C.
[0055] Table 1 Discharge capacity (mAh / g) and 1C cycle 100cls capacity retention rate (%) of the embodiments and comparative examples at different rates
[0056]
[0057] The cycle curves of the embodiment and comparative example at 45°C 1C / 1C 2.0-4.4V are as follows Figure 1 It can be seen that compared with the traditional method, the lithium manganese iron phosphate powder prepared by the present invention has higher discharge capacity and better cycle stability.
[0058] Table 2 Compacted density and particle size distribution of powders in the examples and comparative examples
[0059]
[0060]
[0061] The SEM images of the embodiments and comparative examples are as follows: Figure 2 As shown, from the comparison between the embodiment and the comparative example, it can be seen that compared with the traditional method, the lithium manganese iron phosphate powder prepared by the present invention has a higher compaction density and a more uniform particle size distribution.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density lithium manganese iron phosphate positive electrode material, characterized in that: include: The lithium source, the recovered LiFePO4 intermediate, the carbon source, the dispersant and water are uniformly mixed to obtain a mixed solution A; adding a manganese source into the mixed solution A to obtain a mixed slurry B; Grinding the mixed slurry B and adding a phosphorus source to obtain a mixed slurry C; The mixed slurry C is spray-dried and sintered to obtain lithium iron manganese phosphate powder; Wherein, the recovered LiFePO4 intermediate is recovered from waste lithium iron phosphate batteries.
2. The method for preparing the high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The manganese source is selected from at least one of manganese oxalate, manganese acetate, manganese nitrate, basic manganese carbonate, manganese monoxide, and trimanganese tetraoxide.
3. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: After the grinding, the D50 of the particles is 250-400 nm.
4. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The selected phosphorus source is at least one selected from phosphoric acid, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.
5. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: After the spray drying, the powder particle size is 15 to 30 μm.
6. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The sintering is carried out in an inert atmosphere with an O2 content of <10 ppm.
7. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The specific steps of sintering are: firstly keeping the temperature at 200-400°C for 2-5h, then keeping the temperature at 600-900°C for 3-5h, and finally keeping the temperature at 600-800°C for 5-8h.
8. The method for preparing the high-density lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The D50 of the lithium iron manganese phosphate powder is 0.8-1.2 μm.
9. A high-density lithium iron manganese phosphate positive electrode material prepared by the method according to any one of claims 1 to 8.
10. Use of the high-density lithium manganese iron phosphate positive electrode material according to claim 9 in the preparation of electric vehicles, household storage, backup power supplies, and energy storage power stations.